Peter Faber before the Protestant Reformation - Madrigal Terrazas, SJ, Santiago (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
Peter Faber, known for his special talent in dialogue and human touch as well as for his excellent theological training in Paris, was one of the Jesuits sent by Ignatius of Loyola to handle matters of dialogue with Protestants and the reform of the Catholic Church. Faber participated in the colloquiums at Worms (1540) and at the Diet of Ratsbona (1541). His participation in the Council of Trent was later truncated by a premature death. His writings, especially his Memories, and the notes left by the Carthusian Gerard Kalckbrenner of Hammont taken in conversations with the Saboyan, allow the author of this article to describe the traits of that mission among the Protestants: the insistence by Faber to dialogue in charity and the example of own’s life and his search for common ground; situating this all in the theological debates and the historical context of the time period.